PHYTOCHEMICAL EVALUATION OF RICINUS COMMUNIS LINN. ROOT (ERANDA) OF COLLECTED FROM THREE DIFFERENT REGIONS OF BELGAUM (KARNATAKA) - Dhiman, *Ambika; Hiremath, S.K.; Patil, G.M. (International Journal of Ayurveda and Pharma Research, 2016)
In Ayurveda, the roots of Eranda plant (Ricinus communis Linn.) are used in the treatment of various disorders like Amavata (rheumatism), Jwara (fever) and various types of inflammation. It is important drug used in Panchkarma Basti procedure as Niruha basti drug. This drug is collected by various pharmaceutical companies from anywhere ignoring contaminations. Considering this, a preliminary study has been done to ensure basic phytochemical profile of mentioned regions varieties. Preliminary physicochemical parameters, phytochemical screening was carried out in the study. There was significant difference between all varieties of alcohol and water extracts of this plant. Though present study gives idea for pharmacological and clinical studies at larger scales.